Production of precision K-Carrageenan Microcapsule by Co-Flowing Microfluidic system - Chan, Eng Seng; Pogaku Ravindra (Universiti Malaysia Sabah, 2007)
The formation of hydrogel microcapsule using microfluidic device was investigated in this project. The primary objective of this work is to evaluate the potential of co-flowing microfluidic device in producing quality microcapsule. The first part of this work involved the construction of a co-flowing microfluidic device that can be used to produce hydrogel particle. The second part of the project focused finding the effect of process parameters on the droplet/microcapsule formation behavior and droplet/microcapsule properties. The third part aimed at developing a mathematical model to predict the droplet/microcapsule size from the affecting parameters. The final part investigated the scale-up potential of the studied system. In this research, three types of droplet formation modes were distinguished: dripping, narrowing jetting and widening jetting. The transition points between each type of breakup modes were found to be influenced by the interplay among inertial force, viscous force and interfacial force of the system. The transition points were then compared to a theoretical model. It was also found that the droplet size produced in liquid-liquid system affected by the combined influence of the liquids properties, flow dynamics combinations and geometry of the system setup. A two-stage model was developed and was found to be consistent with the experimental data and the average absolute deviation (AAD) lies within 5% of the calculated values. On the other hand, the breakup mechanism of liquid jets in liquid-liquid system was found to be consistent with the Rayleigh's instability theory and the drop size was well predicted from existing model. In the scale-up study, it was suggested that the droplet formation in the system should remain in the dripping mode. Using the twostage model, a simulation was performed to scale-up the productivity of the liquid-liquid dispersion system. Optimum operating conditions was able to be determined through the simulation.